Pengaruh Akses Media terhadap Status Imunisasi Dasar pada Anak di Indonesia - Nia Musniati; Izza Suraya; Yoli Farradika; Elia Nur A’yunin; Hidayati (ARTERI : Jurnal Ilmu Kesehatan, 2020)
In 2018, an estimated 19.4 million babies worldwide will not be achieved with basic immunization services. About 60% of these children live in 10 countries: Angola, Brazil, Democratic Republic of the Congo, Ethiopia, India, Indonesia, Nigeria, Pakistan, the Philippines, and Vietnam. This study aimed to determine the effect of media access on basic immunization status in Indonesia. This study was carried out using a cross-sectional design by further analyzing Indonesian IDHS data for 2017. The study was conducted from January to March 2020. The number of samples used was 6483 mothers who had children aged 12-23 months with a saturated sample technique. Data processing and analysis using SPSS and data analysis performed was univariate analysis, bivariate using Chi Square test, and multivariate using the Multiple Logistic Regression test. Bivariate results show a significant relationship between reading newspapers, watching television, and frequency of internet access with basic immunization status in Indonesia (P-value <0.05). Multivariate results showed a significant relationship between watching television and frequency of internet access with basic immunization status (P-value <0.05). The most dominant or most influential variable on Indonesia's basic immunization status is watching television with OR = 2,268 (1,754-2,931). Suggestions from this research are that the government promotes proper socialization about the importance of basic immunization in various media, especially in television media.